Faraq perkahwinan bagi pasangan tak sah taraf di Negeri Sembilan - Wan Abdul Fattah Wan Ismail; Hasnizam Hashim; Syahirah Abdul Shukor; Asma Harun (Penerbit Universiti Kebangsaan Malaysia, 2018)
Islam stressed on the importance of a valid marriage. If a marriage does not comply its requirement and conditions according to Shariah, it will raise negative implications not only on the status of the marriage, but also it will effect the status of the child. Hence, the marriage must be separated. Generally, the Muslim scholars define faraq as separation or dissolution of marriage through talaq or otherwise. However, according to Islamic law in Malaysia, faraq is not a dissolution of marriage via talaq, but it is an annulment of marriage due to non-fulfillment of terms and conditions which laid down by Shariah. In context of abiding the conditions and terms to marriage, having a wali is one of the conditions in solemnization of a valid marriage. Marriage which is solemnized by a non-qualified wali such as in cases of illegitimate children will cause the marriage to be separated. Data in this article is obtained from the reported cases tried in the Shariah Courts in Negeri Sembilan. Interviews were conducted with those legal practitioners such as syaria lawyers, religious officers, and judges from Shariah Courts in Negeri Sembilan who deal directly with faraq cases.